Análise e simulação da reação de metanação do dióxido de carbono - Campeiro, Richard Rafael (Universidade Federal de São Carlos, 2021)
With the increasing environmental appeal nowadays, the question arises: how to use carbon dioxide in a way that reduces its impact on the environment? One possibility is the capture of CO2 and its transformation into chemicals. One of the possible reactions is CO2 methanation, which aims to produce CH4 through the reaction between CO2 and H2. There are two possible routes for this methanation, the first is the so-called "Sabatier reaction", in which CO2 reacts with H2 under the presence of a nickel catalyst and the second initially consists of the RWGS (reverse water-gas shift) reaction – which produces carbon monoxide through the hydrogenation of CO2 and then methanation the CO. Obtaining methane through these routes can be a means for the production of synthetic natural gas or it can be used in the production of other hydrocarbons. The methanation reaction was simulated with the software Aspen Plus, in which the reaction equilibrium was performed with the Gibbs reactor and the reaction kinetics was used together with the fixed bed reactor. The results indicated that the determination of the equilibrium constant by the Gibbs reactor with the RKSMHV2 model presented similarities to real conditions. The simulation in isothermal reactors showed a maximum CO2 conversion of 64.9% at 30 bar and 400°C. However, when comparing the simulation results with the experimental data, lags were observed in relation to methane yield, CO selectivity and CO2 conversion. Feeding excess hydrogen gas can be a viable alternative for increasing methane production.
Analysis and simulation of the carbon dioxide methanation reaction
Keywords: Metanação; Simulação; Hidrogenação do CO2; Methanation; Simulation; CO2 hidrogenation; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA